Karakterisasi Dan Potensi Pemanfaatan Palm Oil Mill Effluent (POME) Menjadi Biogas - Ester Melinda; David Andrio; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm oil mills in Indonesia are growing rapidly. This is in line with the waste generated by palm oil, the Palm Oil Mill Effluent (POME) which is increasing. POME is a waste that has potential that can be converted into energy sources, namely biogas. This research was conducted by analyzing the characteristics of POME through pH, chemical oxygen demand (COD) and volatile suspended solid (VSS) as well as its potensial in producing biogas. From this research COD obtained a value of 32000 mg/L. The potensial of biogas energy that is formed through the degradation of organic matter in POME is obtained by 1,35 L/L.day. Keywords: biogas, COD, palm oil mill effluent